New mechanism of producing superheavy Dark Matter - Eugeny Babichev; Dmitry Gorbunov; Sabir Ramazanov (Physics Letters B, 2019)
We study in detail the recently proposed mechanism of generating superheavy Dark Matter with the mass larger than the Hubble rate at the end of inflation. A real scalar field constituting Dark Matter linearly couples to the inflaton. As a result of this interaction, the scalar gets displaced from its zero expectation value. This offset feeds into the energy density of Dark Matter. This mechanism is universal and can be implemented in a generic inflationary scenario. Phenomenology of the model is comprised of Dark Matter decay into inflatons, which in turn decay into Standard Model species triggering cascades of high energy particles contributing to the cosmic ray flux. We evaluate the lifetime of Dark Matter and obtain limits on the inflationary scenarios, where this mechanism does not lead to the conflict with the Dark Matter stability considerations/studies of cosmic ray propagation.